Maternal nesting behaviour by male Mallards - Dane, Charles; Steffen, Willard; Caldwell, Patrick (Wildfowl, 1973)
A wild male Mallard Anas platyrhynchos in full nuptial plumage sat alongside his mate who was on a nest. Later when she left, he sat on the nest for 30 minutes. A penned, hand-reared Greenland Mallard A.p. conboschas in partial moult who had been sitting along his nesting mate, occupied her nest site for 36 days after eggs were exchanged and female apparently deserted the nest. The hormonal balance likely to induce such behaviour is discussed.